Efeito da suplementação aguda de NO3- no desempenho de corredores de fundo - Leal, Ludmila Dias dos Santos (2022)
Nitrate (NO3 -) has been consolidated as an ergogenic capable of optimizing sports performance, especially in untrained individuals due to its vasodilation capacity. This effect contributes to greater support for the exercise. The objective was to evaluate the effect of NO3- supplementation on performance in a progressive test in long-distance runners. We also propose, in an original way, the use of heart rate (HR) together with its by-products - Heart Rate Inflection Point (HRIP) and HR Deflection Point (HRDP) for detection of metabolic transition points (MTP). research of an experimental, double-blind, crossover nature. A sample of 13 men runners from a street running team in the city of Varginha - Minas Gerais were submitted to a progressive incremental test - PIT on a treadmill where the subjects performed the test at 2 different times - Nitrate Moment (NM) and Placebo Moment (PM). NO3 - supplementation was carried out 2 hours before testing with 70 ml of concentrated beet juice rich in NO3- (~6.4mmol NO3 -- 400mg - Beet IT; James White Drinks Ltd, Ipswich, UK) or depleted placebo in NO3 - (0.04 mmol NO3 - >0.8g/L - Beet IT; James White Drinks Ltd, Ipswich, UK). Measurement of HR, Subjective Effort Perception (RPE), time, and final velocity were performed. For data analysis, the Shapiro-Wilk test was used to verify the sample distribution and the Levene test for the homogeneity of variance, and for the analysis of variables, the paired T-test was used. In addition to comparing the means, the delta of variation (Δ) of the results and the size of the sample effect were also determined using the Cohen test (d), with a significance level of p < 0.05. The results revealed that the nitrate was not able to improve the studied parameters, however, we observed a tendency of improvements in the NM about the PM in the variables time, speed, and distance, respectively (d=0.035; d=0.026; d=0.036) a time decrease of about 2-3% (21.04 ± 4.17 x 19.54 ± 3.96 minutes). We did not detect any difference between Maximum Heart Rate (HRMAX), RPE and maximum oxygen volume (VO2MAX) in NM in relation to PM respectively (p=0.573; p=1.108; p= 0.102). The MTP`s showed no statistical difference between NM and PM moments in HRIP and HRDP respectively (p=0,216; p=0.508). Regarding oxygen consumption in HRIP and HRDP, we observed that in NM and PM, they occurred respectively at 37.49 ± 3.00ml.kg.min-1 Vs. 36.98 ± 1.36ml.kg.min- 1 (p=0.562), and 46.77 ± 6.47ml.kg.min-1 vs. 44.45 ± 5.66ml.kg.min-1 (p=0.971), revealing a difference of 9.27 ± 4.76ml.kg.min-1 vs. 7.46 ± 4.95ml.kg.min-1 (p=0.945). The findings on the RPEthreshold also show no statistical difference in the RPEthreshold parameters (p=0.678); HR in the RPEthreshold (p=0.668); Velocity in RPEthreshold (p=0.457); VO2MAX in RPEthreshold (p=0,574). We did not observe statistical differences regarding the printed speed in running in the TMP`s between NM and PM respectively (p=0.562; p=0.971), however, we detected a difference of 2.76 ± 1.42 km/h-1 vs. 2.23 ± 1.48 km/h-1 (p=0.820) between the points. The percentages of Vmax and Vpeak in PTM`s also did not show statistical difference between NM and PM groups in HRIP and HRDP respectively (%Vmax p= 0.524; p= 0.361) - (%Vpeak p=0.598; p=0.295). In summary, nitrate supplementation does not interfere with the performance of amateur long-distance runners during a PIT. However, we obtained a tendency to subtle improvements in NM in all studied variables, which, in practical terms, could contribute to an improvement in the performance of these athletes.